Profilin is involved in G1 to S phase progression and mitotic spindle orientation during Leishmania donovani cell division cycle - Bindu Ambaru; Ganesh Muthu Gangadharan; Hosahalli S. Subramanya; Chhitar M. Gupta (PLoS ONE, 2022)
Profilin is a multi-ligand binding protein, which is a key regulator of actin dynamics and involved in regulating several cellular functions. It is present in all eukaryotes, including trypanosomatids such as Leishmania. However, not much is known about its functions in these organisms. Our earlier studies have shown that Leishmania parasites express a single homologue of profilin (LdPfn) that binds actin, phosphoinositides and poly- L- proline motives, and depletion of its intracellular pool to 50%of normal levels affects the cell growth and intracellular trafficking. Here, we show, employing affinity pull-down and mass spectroscopy, that LdPfn interacted with a large number of proteins, including those involved in mRNA processing and protein translation initiation, such as eIF4A1. Further, we reveal, using mRNA Seq analysis, that depletion of LdPfn in Leishmania cells (LdPfn+/-) resulted in significantly reduced expression of genes which encode proteins involved in cell cycle regulation, mRNA translation initiation, nucleosides and amino acids transport. In addition, we show that in LdPfn+/- cells, cellular levels of eIF4A1 protein were significantly decreased, and during their cell division cycle, G1-to-S phase progression was delayed and orientation of mitotic spindle altered. These changes were, however, reversed to normal by episomal expression of GFP-LdPfn in LdPfn+/- cells. Taken together, our results indicate that profilin is involved in regulation of G1-to-S phase progression and mitotic spindle orientation in Leishmania cell cycle, perhaps through its interaction with elF4A1 protein.